2016
DOI: 10.1002/pd.4812
|View full text |Cite
|
Sign up to set email alerts
|

The use of noninvasive prenatal testing in obstetric care: educational resources, practice patterns, and barriers reported by a national sample of clinicians

Abstract: Advances in cff DNA technology emphasize the need for effective strategies for physicians to develop competency and practice patterns regarding NIPT. Study findings speak to the need for effective educational resources for obstetric providers, not just early adopters of NIPT but also for primary OB/GYNs as they serve in the role of the first point of contact for women considering their prenatal testing options. © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 38 publications
(71 reference statements)
5
30
0
1
Order By: Relevance
“…These findings are consistent with another recent study that found counselling and education resources about cfDNA screening are not being offered as often as the screen itself is offered, in spite of professional society guidelines to the contrary [39]. Indeed, in a recent survey, more than 80% of practicing obstetric care providers reported lack of time as a barrier to counseling patients about cfDNA screening [22]. …”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…These findings are consistent with another recent study that found counselling and education resources about cfDNA screening are not being offered as often as the screen itself is offered, in spite of professional society guidelines to the contrary [39]. Indeed, in a recent survey, more than 80% of practicing obstetric care providers reported lack of time as a barrier to counseling patients about cfDNA screening [22]. …”
Section: Discussionsupporting
confidence: 88%
“…This small sample size is ultimately composed of providers who were willing to participant and discuss their experiences, which may have resulted in responder bias. While we cannot claim generalisability for the themes identified in this small qualitative study, they are consistent with the findings of other studies on the views of providers and patients [21,22,35,38,51] and suggest themes for further exploration. Care was also taken to ensure that study participants reflected a variety of prenatal experiences with respect to clinical setting.…”
Section: Limitationssupporting
confidence: 85%
See 2 more Smart Citations
“…A small number of studies have looked at the views of health professionals regarding NIPT and the need for educational resources for health professionals that are accurate and effective has been highlighted [2330]. Here we aimed to develop and evaluate training resources to support midwives and other health professionals offering NIPT for Down syndrome.…”
Section: Introductionmentioning
confidence: 99%